Validation of ARISCAT Model Score to Predict PostoperativePulmonary Complications in Tertiary Referral Hospital inIndonesia - Alkaff, Muhammad; Pitoyo, Ceva Wicaksono; Heriwardito, Aldy; Koesnoe, Sukamto (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. There are several prediction model score instruments that can help to assess pulmonary preoperative evaluation and it is believed that ARISCAT model score is very simple to do and have good performance, but not widely used. This score has not been yet validated in Indonesia. This study aimed to assess the performance of discrimination and calibration of ARISCAT score in predicting postoperative pulmonary complication who underwent surgery in a tertiary referral hospital in Indonesia. Methods. A retrospective cohort study was conducted to assess the external validation of ARISCAT scores in the Indonesian population. This study involved patients underwent surgery at Cipto Mangunkusumo Hospital in 2017. Several variables were collected such as age, oxygen saturation, history of pulmonary infection, anemia, type of surgery, duration of operation, emergency surgery, and PPC that observed within 30 days after surgery. Discrimination was assessed by the area under the curve (AUC). Calibration was assessed by the Hosmer-Lemeshow test and calibration plot. Results. Of 428 patients studied, PPC was observed in 32% of patients. Discrimination of ARISCAT score was shown by AUC value of 88.2% (CI 95%; 84.1-92.2%). Hosmer-Lemeshow test showed p=0.052 and calibration plot revealed coefficient Jurnal Penyakit Dalam Indonesia | Vol. 6, No. 1| Maret 2019 | 3 Uji Validasi Skor ARISCAT dalam Memprediksi Komplikasi Paru Pascaoperasi di RS Rujukan Tersier di Indonesia r=0.968. Conclusion. ARISCAT model score has good discrimination and calibration performance and can be applied in the Indonesian population.